43. FOOD SAFETY KNOWLEDGE AND PRACTICES OF FOOD BUSINESS OPERATORS IN THAI BINH PROVINCE, IN 2023 (Vietnam Journal of Community Medicine, 2024)
Objective: The study aimed to describe the current status of food safety knowledge and practices among food business operators in Thai Binh Province in 2023.Subject and method: A cross-sectional descriptive study was conducted on 250 food business operators in Thai Binh Province. The study assessed their knowledge and practices using interview questions and assessment sheets.Results: Food safety understanding among packaged food operators (PFOs), food service providers (FSOs), and street food vendors (SFVs) shows comparable levels. PFOs report 83,5% compliance (49,5% Level A, 34,1% Level B), FSOs 83,5% (57,1% Level A, 26,2% Level B), and SFVs 86,7% (68% Level A, 18,7% Level B). FSOs demonstrate the highest adherence at 100% (60,7% Level A, 39,3% Level B), followed by SFVs at 97,3% (53,3% Level A, 44% Level B), with PFOs at 96,3% (17,6% Level A, 74,7% Level B). Key practices like using clean water and utensils exceed 90%, but ensuring ingredient quality and eliminating stagnant water are below 60%. Issues such as wearing jewelry and long nails during food handling are reported at 19% and 21,3%, respectively.Conclusion: When comparing three groups in terms of food safety knowledge and practices, prepackaged food businesses show lower levels than the other two groups. To address this deficiency, increased training and educational outreach on health and food safety are necessary to enhance and maintain their standards, especially among pre-packaged food businesses.
Keywords: Food safety, knowledge, practices, business, Thai Binh.